Performance of magnetic resonance imaging in the diagnosis of axial spondyloarthritis: a systematic literature review. (2nd May 2019) - Jones, Alexis; Bray, Timothy J P; Mandl, Peter; Hall-Craggs, Margaret A; Marzo-Ortega, Helena; Machado, Pedro M
Abstract: Objectives: To summarize the evidence on the performance of MRI for the diagnosis of axial SpA. Methods: This was a systematic literature review of all studies from January 2013 to March 2017 including adult patients with clinically suspected axial SpA undergoing MRI. Studies from a previously published systematic literature review up to January 2013 were also included. Results: Thirty-one studies were included. Six studies demonstrated good sensitivity and specificity for SI joint (SIJ) bone marrow oedema (BMO). Specificity was increased by the presence of other structural lesions alongside BMO, particularly erosions or fat infiltration. Four studies addressed the utility of SIJ fat infiltration, finding good sensitivity but poor specificity. SIJ erosions showed good specificity in five studies. Studies addressing high T1 signal in the SIJ, fluid signal in the SIJ, ankylosis, sclerosis, capsulitis, backfill and vacuum phenomenon reported limited diagnostic value. In the spine, four studies reported moderate sensitivity and specificity for corner inflammatory lesions, and four reported poor sensitivity and specificity for spinal fat infiltration. Five studies evaluated the added value of spinal MRI over SIJ MRI alone, with variable results depending on the cohort. Six studies addressed the effect of acquisition parameters on diagnostic accuracy: fat-saturated T2-weighted imaging and short tau inversion recovery (STIR) imaging showed comparable utility in identifying BMO. Three studies showed that gadolinium was of minimal added value in the detection of BMO. Conclusions: These results confirmed the diagnostic utility of MRI in axial SpA. Performance varied according to the characteristics of the cohort and the number and combination of MRI lesions considered.